CHALLENGES AFFECTING THE PERFORMANCE OF SMALL AND MEDIUM SCALE ENTERPRISES (SMES) IN NIGERIA - Abdullahi, Mohammed Sani; Jakada, Balarabe Abubakar; Kabir, Salwa (Journal of Human Capital Development (JHCD), 2016)
Small and medium scale enterprises (SMEs) have been identified as the catalysts and builders for economic growth and national development for both developed and developing countries, particularly Nigeria. The objective of this study is to investigate the challenges affecting the performance of SMEs in Nigeria. This paper identifies the challenges affecting the performance of SMEs in Nigeria to include financial constraints, infrastructural problems, management problems, marketing problems, technological problems, corruption problem, lack of skill labour, government unfavourable fiscal policy and policy inconsistence’s, inadequate training, socio-cultural problem, strategic planning problem, multiple taxation, and location and business environment problem. But this study discovered that the major challenges that affect the performance of SMEs in Nigeria are finance, infrastructure and training among other challenges which this study adequately focused on. This study suggests that finance, infrastructure and training should be given adequate concentration. Thus, it is recommended that the government should make loan available for SMEs entrepreneurs, interest rate charge should be single digit instead of double digit, and the collateral demanded by the financial institutions before given out any financial assistance should be fear or the collateral should not be demanded when the project embark on can serve as the collateral. There is a need for the government to improve the existing infrastructure such as power supply, transportation, communication, water supply and roads in the country. Lastly, the SMEs entrepreneurs should inculcate the habit of training and developing their management and workforce to build a strong capacity for meeting the challenges of time to embrace and take advantage of development. Keywords: challenges, performance, SMEs, development, growth, Nigeria